A interatividade como tecnologia de governo na docência no ensino médio - Roberto Rafael Dias da Silva (Universidade Estadual de Campinas, 2013)
This paper examines contemporary modes of incorporation of teaching in high school in Brazil. Is serving as inspiration of Foucault's analytic theories, it was considered as a condition of possibility for the centrality of techno-scientific knowledge and the advent of the conditions of cognitive capitalism and entering the teaching profession within the plots of contemporary bio-economy. We examine this text one of the technologies of government that lead to contemporary teaching in this stage of Basic Education: interactivity as a way of thinking. The deployment of this technology suggests the creation of interactive teaching, become effective from a pedagogical action politically useful and economically productive. In this sense, learning network, the future as something immediate and interactive professionalism are some of the strategies deployed technology within this government. The consideration of teachers as a public as well as the multiplication of meanings related to the learning society, leading to production of "pedagogy of connection" that in this analysis, the formation of Teaching excel with specific conditions to think, act and communicate . Finally, this article defends the view that interactivity operates as a technology of government optimizing the constitution of contemporary teaching in high school in Brazil.